Corticosteroids as standalone or add‐on treatment for sore throat - de Cassan, S; Thompson, MJ; Perera, R; Glasziou, PP; Del Mar, CB; Heneghan, CJ; Hayward, G (Cochrane Collaboration, 2020)
Background Sore throat is a common condition associated with a high rate of antibiotic prescriptions, despite limited evidence for the effectiveness of antibiotics. Corticosteroids may improve symptoms of sore throat by reducing inflammation of the upper respiratory tract. This review is an update to our review published in 2012.